Antibacterial Potential of Crude Extracts from Cylindrospermum alatosporum NR125682 and Loriellopsis cavernicola NR117881 - Albert Olufemi Ikhane; Foluso Oluwagbemiga Osunsanmi; Rebamang Anthony Mosa; Andrew Rowland Opoku (Microorganisms)
The challenges of antimicrobial resistance (AMR) to human health have pushed for the discovery of a new antibiotics agent from natural products. Cyanobacteria are oxygen-producing photosynthetic prokaryotes found in a variety of water habitats. Secondary metabolites are produced by cyanobacteria to survive extreme environmental stress factors, including microbial competition. This study presents the antibacterial activity and mechanism of the crude extracts from Cylindrospermum alatosporum NR125682 (A) and Loriellopsis cavernicola NR117881 (B) isolated from freshwater. The cyanobacteria were identified through 16S rRNA sequencing. Crude extracts were sequentially prepared using hexane, dichloromethane, and ethanol consistently. The minimum inhibition concentration (MIC), minimum bactericidal concentration (MBC) using the CSLI microdilution test protocol, and crude extract potential to inhibit the growth of the tested clinical bacteria strains were evaluated. The mechanism of action of the extracts including membrane damage, efflux pump, β-lactamase activity, DNA degradation, and extract–drug interaction was investigated using standard procedures. The hexane extract of B performed the best with a MIC (0.7–1.41 mg/mL) and MBC (1.41–2.81 mg/mL) range. All the crude extracts inhibited efflux pump activity against the bacteria tested. However, the extracts poorly inhibited β-lactamase. The ethanol extract of B exhibited the most appreciable antibacterial activity. The dichloromethane extract of B showed the highest significant DNA degradation potential, when compared with other samples. The extracts exhibited synergism when combined with erythromycin against some test bacteria, indicating primary microbial activity through membrane interactions. Hence, this study demonstrates the significance of cyanobacteria for antibiotic development.